New solutions for error analysis in investigation of elastomer system properties - I. V. Gorelkin; I. M. Agayants (Тонкие химические технологии)
Variety of graphic representations invoked by error presence in solving of singlefactor and multiple-factor tasks, important in elastomer system properties optimization, is considered here